INOVASI ALARM PERSALINAN DI PUSKESMAS KERINCI KANAN - Rizan Hasbullah; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Innovation in local government is essentially intended to improve and support the improved performance of the local government and public service improvement, In health care also requires a service innovation that will provide convenience and comfort for people in the field of kesehata. Therefore exists a birth in health centers of innovation Alarm Kerinci Kanan Siak.Labor Alarm Innovations is a technology-based program that aims to prevent maternal mortality, birth and post-partum health centers working area UPTD Kerinci Kanan.The purpose of this study was to determine how the implementation of this Labor Alarm Innovations and to find out what is a contributing factor and inhibitory in the innovation process. This study using purposive sampling technique with qualitative research using a descriptive approach and the data required both primary and secondary data obtained by observation, interview and documentation for further analysis. The results of this study indicate that deliveries in health centers Innovation Alarm Kerinci Kanan has been in line with expectations. The supporting factors and obstacles of this deliveries alarm innovation is technology applications, the quality of human resources and infrastructure that already supports. Keywords: Innovation, Services health.